Culture, Institutions and Government Attitudes towards New Firm Entry - Rui Baptista (Max Planck Institute for Research into Economic Systems, 2004)
This paper examines the relationship between cultural values, political institutions and government regulation of entry. For this, it couples data for 53 countries from a variety of sources in comparative political economy and cross-cultural psychology. A society's general attitude towards risk and uncertainty and power inequality are embedded in its institutions; hence, such values should mediate the intensity with which economic incentives affect regulatory procedures and outcomes. Results suggest that entry regulation levels are correlated with the way people in different countries deal with risk and uncertainty and accept inequality of power in their dealings with government institutions. Moreover, these intrinsic cultural values act as moderators for the correlation between economic and political variables, and regulatory intensity. Regulation thus emerges a response from government institutions to societies' needs deriving from cultural values.
Keywords: 330; Unternehmensgründung; Markteintritt; Kulturpsychologie; Public Choice; Schätzung; Welt